2014
DOI: 10.1016/j.krcp.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The association between mortality and abdominal aortic calcification and relation between its progression and serum calcium concentration in chronic hemodialysis patients

Abstract: BackgroundThe composite summary score (range, 0–24) of abdominal aortic calcification (AAC) devised by Kauppila et al is a simple method of assessing AAC severity. However, few studies have been conducted to determine an optimal AAC cutoff score for the prediction of mortality or to investigate the relation between mineral metabolism and AAC progression using the scoring system.MethodsThe medical records of 112 patients on hemodialysis who had undergone simple lateral lumbar radiography every 6 months from Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
(59 reference statements)
1
20
0
2
Order By: Relevance
“…Routine blood tests were performed immediately including hemoglobin, creatinine, albumin, hypersensitive C reactive protein (hs-CRP), calcium (corrected), phosphate, and intact parathyroid hormone values. Corrected calcium levels were calculated using the following formula [11]: corrected calcium = calcium + 0.8 × (4 – serum albumin). Blood samples for s-Klotho measurement were centrifuged, aliquoted in vials, and stored at –80°C until assay.…”
Section: Methodsmentioning
confidence: 99%
“…Routine blood tests were performed immediately including hemoglobin, creatinine, albumin, hypersensitive C reactive protein (hs-CRP), calcium (corrected), phosphate, and intact parathyroid hormone values. Corrected calcium levels were calculated using the following formula [11]: corrected calcium = calcium + 0.8 × (4 – serum albumin). Blood samples for s-Klotho measurement were centrifuged, aliquoted in vials, and stored at –80°C until assay.…”
Section: Methodsmentioning
confidence: 99%
“…Arrows indicate calcification on the anterior and posterior wall of the abdominal aorta adjacent to vertebrae L1-L4. Ogawa et al 2009;Nitta and Ogawa 2011;An and Son 2013;Kwon et al 2014). Two nephrologists individually determined VC scores on plain radiographs without information about patients.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Previous studies illustrated that high or meaningful VC scores of artery or aorta on plain radiographs are associated with CAD events in dialysis patients. (Blacher et al 2001;Adragao et al 2004;An et al 2009An et al , 2010Ogawa et al 2009;Nitta and Ogawa 2011;An and Son 2013;Kwon et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed presence of abdominal aortic calcification was associated with all-cause mortality and cardiovascular mortality in haemodialysis dialysis (HD) patients. 8,9 Severity of abdominal aortic calcification is also significantly associated with diastolic dysfunction and predicts all-cause mortality and nonfatal cardiovascular events in HD patients. 1 However, the association between acute CAD and AAC in peritoneal dialysis (PD) patients is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal aortic calcification has also frequently been used for the prediction of CAD in dialysis patients. Studies showed presence of abdominal aortic calcification was associated with all‐cause mortality and cardiovascular mortality in haemodialysis dialysis (HD) patients . Severity of abdominal aortic calcification is also significantly associated with diastolic dysfunction and predicts all‐cause mortality and nonfatal cardiovascular events in HD patients .…”
mentioning
confidence: 99%